Postmarket studies required by the US Food and Drug Administration for new drugs and biologics approved between 2009 and 2012: cross sectional analysis. (24th May 2018) - Wallach, Joshua D; Egilman, Alexander C; Dhruva, Sanket S; McCarthy, Margaret E; Miller, Jennifer E; Woloshin, Steven; Schwartz, Lisa M; Ross, Joseph S
Abstract: Objectives: To characterize postmarketing requirements for new drugs and biologics approved by the US Food and Drug Administration (FDA), and to examine rates and timeliness of registration, results reporting, and publication of required prospective cohort studies, registries, and clinical trials. Design: Cross sectional analysis. Setting: Postmarketing requirements for all new drugs and biologics approved by the FDA between 1 January 2009 and 31 December 2012, with follow-up up to 15 November 2017. Main outcome measures: Postmarketing requirements and their characteristics known at the time of FDA approval, including FDA authority, study design, and study characteristics. Rates and timeliness of registration and results reporting on ClinicalTrials.gov and publication in peer reviewed journals of required prospective cohort studies, registries, and clinical trials. Results: Between 2009 and 12, the FDA approved 97 new drugs and biologics for 106 indications with at least one postmarketing requirement at the time of first approval, for a total of 437 postmarketing requirements. Postmarket study descriptions were short (median word count 44 (interquartile range 29-71)) and often lacked information to determine an up to date progress (131 (30%)). 220 (50.3%) postmarketing requirements were for new animal or other studies (including pharmacokinetic studies); 134 (30.7%) were for prospective cohort studies, registries, and clinical trials; and 83 (19.0%) were for secondary analyses or follow-up studies. Of 110 clinical trials, 38 (34.5%), 44 (40.0%), 62 (56.4%), 66 (60.0%), and 98 (89.1%) did not report enough information to establish use of randomization, comparator type, allocation, outcome, and number of patients to be enrolled, respectively. Of 134 required prospective cohort studies, registries, and clinical trials, 102 (76.1%) were registered on ClinicalTrials.gov; of 50 registered and completed studies, 36 (72.0%) had reported results on ClinicalTrials.gov. Among 65 completed studies, 47 (72.3%) had either reported results or were published a median of 47 months (interquartile range 32-67) after FDA approval. 32 (68.1%) of these 47 studies did not report results publicly by the time of their original FDA report submission deadline. Conclusions: Postmarketing requirements for new drugs and biologics were often briefly described and did not contain enough information to characterize study designs. Approximately three quarters of postmarketing requirements for prospective cohort studies, registries, and clinical trials were registered on ClinicalTrials.gov, and nearly three quarters of completed studies reported results or were published, suggesting that at least a quarter of these required studies are not being publicly disseminated.